Differentiation of benign nevoid rests and metastatic melanoma in sentinel lymph node biopsy. Issue 2 (9th February 2023) - Phillipos, Joseph; Khan, Afaq; Jayasuriya, Neil
Abstract: Patients with cutaneous melanoma routinely undergo sentinel lymph node (SLN) biopsy. If this first lymph node is clear, the entire lymph node basin is very likely to be free from the metastatic disease. Lymph node analysis is therefore of great importance with respect to prognostication and further management. Various cell types, including benign nevoid rests, can mimic metastatic melanomatous cells in the SLN. There is no standardized method to differentiate naevoid rests from metastatic melanoma. Diagnosis is based on cell location, morphology and multiple immunohistochemical techniques, with no single test being completely diagnostic. We present a patient with Lentigo Maligna melanoma, who was found to have benign nevoid rests on SLN biopsy, and discuss the diagnostic tests and considerations in differentiating benign nevoid rests from metastatic melanoma.